EUROPEAN ENTREPRENEURSHIP IN TIMES OF CRISIS: REALITIES, CHALLENGES AND PERSPECTIVES - Andreea-Oana Iacobuta; Oana-Ramona Socoliuc (CES Working Papers, 2014)
The role of entrepreneurship in economic growth and development has been largely debated and acknowledged, both in literature and in policy making. Wihin the context of the present crisis, at a European level, entrepreneurship development is seen as the main solution for job creation and sustainable economic growth. As a consequence, there have been several calls and initiatives to make entrepreneurship the growth engine of European economy and to put the principle of “think small first” at the core of national and European policies. This paper discusses the challenges and the perspectives for entrepreneurship development in European countries from the point of view of the three areas of intervention proposed by Entrepreneurship 2020 Action Plan. The research methods are the analysis of different reports and policy papers and comparative analysis of statistical data from international databases. The main findings confirm the differences in entrepreneurial activity, level and nature of entrepreneurship existing at European level during the crisis, and also point out the strengths and weaknesses of European countries in the three areas proposed by the 2020 Action Plan.